Affective Infrastructures: Toward a Cultural Neuropsychology of Sport - Heywood, Leslie L. (Frontiers in Evolutionary Neuroscience, 2011)
Recently there has been a turn toward considerations of embodiment, cognition, and context in sport studies. Many researchers have argued that the traditional focus on clinical psychology and performance enhancement within the discipline is incomplete, and now emphasize the importance of athletes’ social and familial contexts in a research paradigm that examines interconnections between movement, cognition, emotion, and the social and cultural context in which movement takes place. While it is important that the sport studies focus is being expanded to consider these interactions, I will argue that this model is still incomplete in that it is missing a fundamental variable – that of our evolutionary neurobiological roots. I will use the work of affective neuroscientists Jaak Panksepp and Stephen Porges to show that because sport so clearly activates neural systems that function at both proximate and ultimate levels of causation, it can be seen to serve fundamental needs for affective balance. A neurobiology of affect shows how the evolution of the mammalian autonomic nervous system has resulted in neurophysiological substrates for affective processes and stress responses, and has wide-ranging implications for sport studies in terms of suggesting what forms of coaching might be the most effective in what context. I propose the term cultural neuropsychology of sport as a descriptor for a model that examines the relationships between neurophysiological substrates and athletes’ social and familial contexts in terms of how these variables facilitate or fail to facilitate athletes’ neuroceptions of safety, which in turn have a direct impact on their performance. A cultural neuropsychological model of sport might thereby be seen to elaborate a relationship between proximate and ultimate mechanisms in concretely applied ways.